2022
DOI: 10.3389/fendo.2022.1041464
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of EU-TIRADS and ACR-TIRADS in risk stratification of pediatric patients with thyroid nodules

Abstract: BackgroundPediatric thyroid nodules have a lower prevalence but a higher rate of malignancy (ROM) than those in adults. Ultrasound features suspected of malignancy lead to fine needle aspiration biopsy (FNAB) and subsequent cytological determination, upon which management is decided. Based on the characteristics of ultrasound, to standardize clinician decisions and avoid unnecessary FNAB, the European Thyroid Association and the American Radiology College have established guidelines for Thyroid Imaging, Report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
1
1
0
Order By: Relevance
“…Consistent with previous literature, our cohort showed a predominance of younger women [2,17] and papillary histology [4,18] . The TIRADS malignancy risk stratification also aligned with prior studies, with most cancers arising from moderately suspicious nodules [19,20] . However, our study found a high prevalence of capsular invasion (58.7%) and cervical lymph node metastasis (28.5%) among patients with thyroid carcinoma.…”
Section: Key Findings and Implications From A Study Of Thyroid Carcin...supporting
confidence: 59%
“…Consistent with previous literature, our cohort showed a predominance of younger women [2,17] and papillary histology [4,18] . The TIRADS malignancy risk stratification also aligned with prior studies, with most cancers arising from moderately suspicious nodules [19,20] . However, our study found a high prevalence of capsular invasion (58.7%) and cervical lymph node metastasis (28.5%) among patients with thyroid carcinoma.…”
Section: Key Findings and Implications From A Study Of Thyroid Carcin...supporting
confidence: 59%
“…Table 2 summarizes the ROM for the cases of ours that had histologic follow-up in the context of previously published pediatric cohorts [5,6,[45][46][47][48][49][50][51][52], which will be discussed further below.…”
Section: Acr Ti-rads Results From the Pediatric Literature Including ...mentioning
confidence: 99%
“…For the combined score, the AUC is 0.89, standard error is 0.077, and 95% confidence interval is 0.81-0.97. Although none of the different ultrasound risk stratification systems have been widely adopted worldwide like the Bethesda system has been for reporting thyroid FNA results [29], in pediatrics, the greatest number of general studies (to our knowledge 11, including our own) have involved ACR TI-RADS [5,6,[45][46][47][48][49][50][51][52]. Seven pediatric studies have examined the ATA grading system [5,6,50,61,[80][81][82], and a smaller number of studies have looked at EU-TIRADS [5,50,52,74], K TI-RADS [5,50,83] (one compared the diagnostic performance of the 2021 K TI-RADS criteria to those of 2016 K TI-RADS) [83], Kwak TI-RADS [46,81], or AACE/ACE/AME [5] in children and adolescents.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…FNAB is not widely accepted by patients because it is an invasive examination and its uncertain results. [6,7] The progressive knowledge analytics contributed by arti cial intelligence (AI) has hugely dilated researchers' capability for purposeful discovery. The application of machine learning (ML), a subset of AI, gives novel clinical insights for enhancing prognosis and diagnosis accuracy.…”
Section: Introductionmentioning
confidence: 99%